Acesso e permanência no ensino superior: estratégias de governamento da conduta de alunos surdos incluídos - Goularte, Ravele Bueno (2014)
This dissertation presents a study on inclusion of deaf students in the Federal University of Santa Maria (UFSM), an institution that presently has 15 deaf students enrolled in different undergraduate courses. Given this situation, there is a need to analyze how the processes of government of deaf students have developed in UFSM. The study was focused on both the admission and permanence of such students in the academic contexts of the University, aiming at analyzing government actions for access to UFSM that capture deaf students, understanding the government strategies that keep deaf students included and problematizing the effects of inclusion. The research took UFSM as its scenario and adopted a post-structuralist perspective on education, articulated with Foucauldian theorizations; Foucault s notion of governmentality and his understanding of government were central to this study. It was possible to perceive that, during the access procedures, there has been a strong investment in linguistic and cultural issues related to the deaf subject, for instance, edict and entrance examination in Brazilian Sign Language (Libras), differentiated writing evaluation, and extension project Libras Tri, among others. Thus, the subjects have been governed and captured through linguistic and cultural issues during their access to the University. Government strategies have also been designed to keep these subjects included after their admission, for example, deaf students have been exalted, tutored and become invisible to remain included. In the same way, in order to remain included, deaf students design strategies of government of self, such as the categories selected in this study: what matters is to be included and ways of communicating . From the analyses, it was concluded that such strategies of government of self and others have been operated for the deaf to invest in themselves and become productive and useful.